1994
DOI: 10.1523/jneurosci.14-04-02047.1994
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced impairment in declarative memory performance in adult humans

Abstract: Glucocorticoids (GCs) have a variety of effects on the brain including site-preferential, inhibitory effects on hippocampal neurons. In the case of dexamethasone (DEX), extended rather than single-dose treatment in vivo may be required for binding to brain rather than peripheral (e.g., pituitary) GC receptors and for maximizing other biologic effects in hippocampus (e.g., GC receptor downregulation, inhibition of glucose transport). Based on the contributory role of hippocampal neurons in declarative memory pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
223
3
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(244 citation statements)
references
References 38 publications
13
223
3
5
Order By: Relevance
“…Furthermore, stressful experiences may additionally modulate glucocorticoid levels [33], and aged individuals may be more vulnerable to such external influences than younger individuals. High levels of glucocorticoids have been shown to correlate with impaired hippocampal-dependent cognitive function in rodents [3], tree shrews [41,42], and humans [30,40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stressful experiences may additionally modulate glucocorticoid levels [33], and aged individuals may be more vulnerable to such external influences than younger individuals. High levels of glucocorticoids have been shown to correlate with impaired hippocampal-dependent cognitive function in rodents [3], tree shrews [41,42], and humans [30,40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ketamine is known to produce increases in plasma cortisol (Krystal et al 1994;Fahringer et al 1974;Clarke et al 1974;Oyama et al 1970) and glucose (Kaniaris et al 1975;Clarke et al 1974), and this group has reported cognitive effects of glucose and insulin (Newcomer et al 1994a; Newcomer et al in press;Craft et al 1993;Craft et al 1996) and glucocorticoids (Newcomer et al 1994b) in humans, motivating the measurement of these variables to rule out confounds to the interpretation of cognitive effects. For similar reasons, plasma epinephrine and norepinephrine were measured with a single isotope derivative (radioenzymatic) method (Shah et al 1985).…”
Section: Plasma Assaysmentioning
confidence: 99%
“…Beckwith et al, 1986) and negative (e.g. Newcomer et al, 1994;Kirschbaum et al, 1996) effects of GC on memory. For example, Lupien et al (2002) found that administration of metrapone, which inhibits cortisol secretion, increases the rate of forgetting in young adults, and that GC replacement reverses this effect.…”
Section: Introductionmentioning
confidence: 99%